How to Unleash the Potential of the Portuguese Registry of Intensive Care Medicine? - João João Mendes; Inês Amaral; João Gonçalves Pereira; José Artur Paiva; Paulo Figueiredo; Pedro Póvoa; Teresa Guimarães; Paulo Mergulhão; on behalf of the RNMI Study Group (Acta Médica Portuguesa)
N/A